2021
DOI: 10.1080/21655979.2021.1930753
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the key genes and pathways involved in B cells in primary Sjögren’ s syndrome

Abstract: Primary Sjögren' s syndrome (pSS) is a relatively common autoimmune disease, which mainly involves the exocrine glands, causing dry eye, dryness of mouth, fatigue and pain in the joints, thus severely affecting the normal lives of patients. B cell populations are considered to play an important role in their pathogenesis and pSS patients are generally characterized by exhibiting biological signs of B cell activation. Moreover, another important characterized change in the peripheral blood of pSS patients is fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Using weighted gene co-expression network analysis (WGCNA), Yao et al identified key genes and pathways in SS ( 15 ). Lei and Zhang identified key genes and pathways involved in B cells in patients with pSS ( 16 ). However, these studies used fewer datasets with a small sample-size and conducted no experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…Using weighted gene co-expression network analysis (WGCNA), Yao et al identified key genes and pathways in SS ( 15 ). Lei and Zhang identified key genes and pathways involved in B cells in patients with pSS ( 16 ). However, these studies used fewer datasets with a small sample-size and conducted no experimental validation.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Yao et al applied weighted gene coexpression network analysis to identify the potential pathways and hub genes that may be involved in pSS development [ 7 ]. Moreover, gene coexpression modules and hub genes in peripheral blood and parotid tissue associated with B cell levels in pSS were identified by Lei and Zhang [ 8 ]. The substantial pathogenesis-related processes of pSS have been studied, but researchers still need to elucidate the exact pathogenesis and the key pathogenic factor of the disease.…”
Section: Introductionmentioning
confidence: 99%